Sharia Financial Literacy as an Ethical Pillar of the Urban Muslim Economy in the Digital Era - Vaniesa Febriyawati; Farras Lulu Ramadhani; Sumarta Sumarta; Farhan Farhan (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2026)
This study aims to examine the role of Islamic financial literacy in shaping economic ethics among urban Muslims in the digital era. In the context of increasingly complex financial life and the deepening penetration of technology in urban society, Islamic financial literacy serves as a critical foundation for fostering ethical economic behavior based on Islamic principles. The research adopts a qualitative design using a descriptive approach and library research, analyzing both classical and contemporary literature on Islamic economics, Islamic ethics, and urban financial behavior. The main findings reveal that a higher level of Islamic financial literacy positively correlates with ethical decision-making, especially regarding the use of sharia- compliant digital financial services. The study also identifies challenges such as gaps in conceptual understanding and the dominance of conventional financial products in the digital market. The implications highlight the need for more systematic and integrated educational strategies to enhance awareness and engagement of urban Muslims in the Islamic economic ecosystem. The study concludes that Islamic financial literacy is not merely a technical knowledge component but a spiritual instrument that sustains the integrity of economic life in the modern era.